2012
DOI: 10.1161/strokeaha.112.650390
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Cerebrospinal Fluid Ceramide Profile After Subarachnoid Hemorrhage

Abstract: Background and Purpose-The purpose of this study was to investigate changes in the cerebrospinal fluid sphingolipid profile in patients with subarachnoid hemorrhage in relation to the occurrence of symptomatic vasospasm and outcome at hospital discharge. Methods-The ceramide profile in the cerebrospinal fluid was determined by mass spectrometry in control subjects and patients with Fisher 3 grade subarachnoid hemorrhage within 48 hours of the bleed. Patients were prospectively followed and subcategorized based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…Elevated levels of C26 ceramide were found in cerebrospinal fluid of patients with aneurismal subarachnoid hemorrhage 38 . Even though the excess was negligible when compared to other ceramides (C18:0, C24:0, C24:1), the difference to the control group was statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…Elevated levels of C26 ceramide were found in cerebrospinal fluid of patients with aneurismal subarachnoid hemorrhage 38 . Even though the excess was negligible when compared to other ceramides (C18:0, C24:0, C24:1), the difference to the control group was statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…Institutional Review Board approval was obtained before study initiation, and written informed consent was required to participate in this study. The study design, including inclusion and exclusion criteria for both cases and controls, was previously described (Testai et al, ). Indicators of stroke severity commonly used in clinical practice, including Glasgow Coma Scale and World Federation of Neurological Surgeons Scale, were determined at admission.…”
Section: Methodsmentioning
confidence: 99%
“…Ceramide (Cer), in particular, participates actively in neural and oligodendroglial cell death and poststroke inflammation (Kilkus et al, ; Testai et al, ; Yu et al, ; Farooqui et al, ; Qin et al, ). We have previously shown that Cer levels increase in the cerebrospinal fluid (CSF) of SAH survivors, particularly in those with poor neurological outcome (Testai et al, ), an observation suggesting that this deleterious mediator could mediate brain injury in this condition. The detrimental effects of Cer are balanced by sphingosine‐1‐phosphate (S1P), which is a proangiogenic and prosurvival sphingolipid that affects vascular diameter after SAH (Tosaka et al, ; Pyne and Pyne, ).…”
mentioning
confidence: 99%
“…In the CSF of patients with SAH, ceramide is increased and an activation of sphingomyelinae (ASMase), S1P-lyase, and glucosylceramide synthase (GCS) lead to an alteration in the production of protective (S1P) in favor of deleterious (Ceramide) sphingolipids. (175, 177) Using SphK1 −/− mice and S1PR antagonism (JTE013), SAH significantly presented an increase in myogenic tone and JTE013 can fully reverse the myogenic tone augmentation both in vivo and in vitro , which reveals a critical role of S1P signaling pathway as a mediator of increased myogenic tone in SAH. (178) Interestingly, S1P 3 receptors are also reported to mediate the potent constriction of cerebral arteries by S1P,(40) thus providing a novel target of S1P 1 /S1P 3 system in regulating the vascular response after SAH.…”
Section: Stroke and The Sphingolipid Pathwaymentioning
confidence: 98%
“…(32, 37, 38, 175179) S1P was first found to induce vasoconstriction in canine basilar artery and SPC was determined to be a novel mediator of Rho-kinase induced cerebral vasospasm and act as a proinflammatory mediator in cerebral arteries. Further, SPC cerebrospinal fluid (CSF) levels are elevated in SAH patients.…”
Section: Stroke and The Sphingolipid Pathwaymentioning
confidence: 99%